Composite catalyst for decomposing positive electrode material lithium supplement agent, preparation method and application
By doping the conductive carbon and metal element composite catalyst, the problem of irreversible loss of lithium ions in lithium-ion batteries is solved, the energy density and cycle life of the battery are improved, and the efficient release and compensation of lithium ions are achieved.
Patent Information
- Application Number
- CN202411438894.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-17
AI Technical Summary
During the charging and discharging process of the first circle of lithium-ion batteries, the formation of solid electrolyte membranes leads to irreversible loss of lithium ions, which reduces the reversible capacity and cycle life of the battery. In addition, the existing positive electrode materials supplement lithium-ion agents have poor conductivity, difficulty in transferring electrons and decomposition potential. High, it is difficult to effectively compensate for lithium ion losses.
Using a composite catalyst composed of nitrogen-doped conductive carbon and metal elemental materials (such as nickel, cobalt, manganese) is prepared by sintering and mixing methods to improve the conductivity and catalytic activity of lithium supplements, reduce the decomposition potential of organic lithium salts, and promote lithium Release of ions.
It significantly improves the first Coulomb efficiency and cycle life of lithium-ion batteries, enhances the conductivity and catalytic effect of lithium supplement agents, reduces the irreversible consumption of lithium ions, and is suitable for a wide range of lithium-ion batteries, improving the energy density of the battery. and cycle stability.
Smart Images

Figure CN119318982A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials for lithium ion batteries, and in particular to a composite catalyst for decomposing a positive electrode material lithium supplement, a preparation method and an application thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, long cycle life and high safety performance, and are expected to become one of the main power and energy storage batteries in the future. However, during the first cycle of charging and discharging, lithium ions will form a solid electrolyte film on the surface of the negative electrode material, causing irreversible loss of lithium ions, which reduces the reversible capacity and cycle life of lithium-ion batteries.
[0003] Generally speaking, matching excess positive electrode can effectively alleviate the impact of irreversible loss of lithium ions on capacity and cycle life. However, excessive positive electrode often reduces the utilization rate of materials and causes a decrease in battery energy density. Pre-lithiation technology can be used to compensate for the irreversible loss of lithium during the first cycle of charge and discharge, thereby achieving a significant increase in the energy density and cycle life of the entire battery, mainly including positive electrode pre-lithiation and negative electrode pre-lithiation.
[0004] Lithium metal powder and lithium foil are very sensitive to air and moisture, which greatly limits the commercial application of negative electrode pre-lithiation. The pre-lithiation method of adding additives to the positive electrode has the advantages of high lithium replenishment capacity and safe and controllable, and has received widespread attention. It is particularly necessary to provide a positive electrode material lithium replenisher with low decomposition voltage and good conductivity.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a composite catalyst for decomposing a lithium supplement agent for positive electrode materials, a preparation method and an application thereof, wherein the composite catalyst can overcome the problems of poor conductivity, difficult electron transfer and high decomposition potential of organic lithium salts with lithium supplementation effect.
[0007] The present invention is achieved in that:
[0008] In a first aspect, the present invention provides a composite catalyst for decomposing a positive electrode material lithium supplement, comprising nitrogen-doped conductive carbon and a metal element, wherein the metal element is selected from at least one of nickel element, cobalt element and manganese element, and the nitrogen in the nitrogen-doped conductive carbon exists in the form of pyridinic nitrogen, pyrrolic nitrogen, graphitic nitrogen and at least one of nitrogen oxide groups.
[0009] In an optional embodiment, the mass fraction of the metal element in the composite catalyst is 1 wt%-20 wt%.
[0010] And / or, the mass fraction of nitrogen in the composite catalyst is 1wt%-4wt%.
[0011] In an optional embodiment, the mass fraction of the metal element in the composite catalyst is 3wt%-11wt%.
[0012] And / or, the mass fraction of nitrogen in the composite catalyst is 1.5wt%-3wt%.
[0013] In a second aspect, the present invention provides a method for preparing a composite catalyst for decomposing a positive electrode material lithium supplement as described in any one of the aforementioned embodiments, comprising: sintering a mixture of a conductive carbon material, a nitrogen-containing organic matter and a metal source corresponding to a metal element to obtain the composite catalyst, wherein the sintering atmosphere is an inert gas.
[0014] In an optional embodiment, the conductive carbon material is selected from at least one of carbon nanotubes, acetylene black, activated carbon, Ketjen black, mesoporous carbon and graphene.
[0015] And / or, the nitrogen-containing organic matter is selected from at least one of melamine, dicyandiamide and urea;
[0016] And / or, the preparation of the mixture comprises: mixing the conductive carbon material, the nitrogen-containing organic matter and the metal source by a solid phase mixing method.
[0017] In an optional embodiment, the sintering step temperature is 600°C-1100°C, the time is 1h-5h, and the sintering atmosphere is an inert atmosphere;
[0018] and / or, the heating rate of the sintering step is 2°C / min-9°C / min;
[0019] And / or, after the sintering step, the sintered product is cooled, crushed and sieved to obtain the composite catalyst.
[0020] In a third aspect, the present invention provides a positive electrode material lithium supplement, comprising an organic lithium salt and the composite catalyst described in any one of the aforementioned embodiments, wherein the mass ratio of the organic lithium salt to the composite catalyst is 2-10.
[0021] In an optional embodiment, the mass ratio of the organic lithium salt to the composite catalyst is 6-9;
[0022] And / or, the organic lithium salt is selected from at least one of lithium oxalate, lithium squarate and lithium citrate.
[0023] In a fourth aspect, the present invention provides a method for preparing the positive electrode material lithium supplement agent described in the aforementioned embodiment, comprising: mixing the organic lithium salt and the composite catalyst by a solid phase mixing method and a liquid phase mixing method to obtain the positive electrode material lithium supplement agent.
[0024] In a fifth aspect, the present invention provides a positive electrode material, comprising the positive electrode material lithium supplement agent described in the aforementioned embodiment.
[0025] The present invention has the following beneficial effects:
[0026] The conductive carbon in the composite catalyst of the present invention can be used as a conductive additive to improve the conductivity of the lithium supplement agent; the metal element and the nitrogen element as catalytic active sites can enhance the binding ability and electron transfer with the organic lithium salt, change the electron cloud distribution around the lithium salt, significantly reduce the reaction activation energy, realize the reduction of the decomposition potential of the organic lithium salt, catalyze and accelerate the decomposition of the lithium supplement additive, thereby accelerating the Li + of release. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0028] Figure 1 This is a SEM photograph of the lithium-ion battery additive prepared in Example 2.
[0029] Figure 2 This is a SEM photograph of the lithium-ion battery additive prepared in Example 5.
[0030] Figure 3 This is the XRD spectrum of the lithium ion battery additive prepared in Example 10.
[0031] Figure 4 This is the first charging curve of the lithium-ion battery additive positive electrode sheet prepared in Example 5.
[0032] Figure 5 The discharge capacity retention rate of the soft-pack batteries assembled in Example 5 and Comparative Example 4. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0034] In sodium-ion batteries, nitrogen-doped carbon can be used as a catalyst for sodium supplements such as sodium oxalate. However, for lithium supplements such as lithium oxalate, since lithium oxalate is more difficult to decompose than sodium oxalate and has a higher decomposition potential, the effect of using nitrogen-doped carbon alone as a catalyst for lithium oxalate is limited.
[0035] An embodiment of the present invention provides a composite catalyst for decomposing a positive electrode material lithium supplement, comprising nitrogen-doped conductive carbon and a metal element, wherein the metal element is selected from at least one of nickel element, cobalt element and manganese element, and the nitrogen in the nitrogen-doped conductive carbon exists in the form of pyridinic nitrogen, pyrrolic nitrogen, graphitic nitrogen and at least one of nitrogen oxide groups.
[0036] The conductive carbon in the composite catalyst of the present invention can be used as a conductive additive to improve the conductivity of the lithium supplement agent; the metal element and the nitrogen element as catalytic active sites can enhance the binding ability and electron transfer with the organic lithium salt, change the electron cloud distribution around the lithium salt, significantly reduce the reaction activation energy, realize the reduction of the decomposition potential of the organic lithium salt, catalyze and accelerate the decomposition of the lithium supplement additive, thereby accelerating the Li + of release.
[0037] In some embodiments, the mass fraction of the metal element in the composite catalyst is 1wt%-20wt%, specifically 1wt%, 5wt%, 10wt%, 15wt%, 20wt% or any value between 1wt%-20wt%. In theory, the increase in the content of the metal element is conducive to increasing the number of catalytic active sites, but too high a content will cause the catalytic effect to decrease, possibly because the active sites are partially covered. In some embodiments, the mass fraction of the metal element in the composite catalyst is 3wt%-11wt%.
[0038] In some embodiments, the mass fraction of nitrogen in the composite catalyst is 1wt%-4wt%, specifically 1wt%, 2wt%, 3wt%, 4wt% or any value between 1wt%-20wt%. In theory, an increase in nitrogen content is beneficial to increase the number of catalytic active sites, but too high a content will reduce the catalytic effect, possibly because the active sites are partially covered. In some embodiments, the mass fraction of nitrogen in the composite catalyst is 1.5wt%-3wt%.
[0039] An embodiment of the present invention also provides a method for preparing a composite catalyst for decomposing a positive electrode material lithium supplement as described in any one of the aforementioned embodiments, comprising: sintering a mixture of a conductive carbon material, a nitrogen-containing organic matter and a metal source corresponding to a metal element to obtain the composite catalyst, wherein the sintering atmosphere is an inert gas.
[0040] In some embodiments, the conductive carbon material is selected from at least one of carbon nanotubes, acetylene black, activated carbon, Ketjen black, mesoporous carbon and graphene. In addition to having good electrical conductivity, the conductive carbon material also has a large specific surface area, which is conducive to increasing the contact between organic lithium and active sites.
[0041] In some embodiments, the nitrogen-containing organic matter is selected from at least one of melamine, dicyandiamide and urea.
[0042] In some embodiments, the metal source is a metal oxide.
[0043] In some embodiments, the preparation of the mixture includes: mixing the conductive carbon material, nitrogen-containing organic matter and metal source by a solid phase mixing method, specifically, including but not limited to ball milling, high mixing and plowshare mixing. Compared with the liquid phase mixing method, solid phase mixing does not require drying, which is conducive to simplifying the process.
[0044] In some embodiments, the sintering step temperature is 600°C-1100°C, specifically 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C or any value between 600°C-1100°C; the time is 1h-5h, specifically 1h, 2h, 3h, 4h, 5h or any value between 1h-5h. The sintering atmosphere is an inert atmosphere. During the sintering process, the nitrogen-containing organic matter decomposes and the metal source is reduced to a single substance. Therefore, a sufficiently high temperature and a sufficiently long time are required to ensure that the nitrogen-containing organic matter is completely decomposed and the metal source is fully reduced. However, if the decomposition temperature is too high, it will affect the porous structure of the conductive carbon material. If the sintering time is too long, it will meaninglessly increase energy consumption.
[0045] In some embodiments, the heating rate of the sintering step is 2°C / min-9°C / min, specifically 2°C / min, 5°C / min, 7°C / min, 9°C / min or any value between 2°C / min and 9°C / min. Too fast a heating rate may increase the stress of the conductive carbon material.
[0046] In some embodiments, after the sintering step, the sintered product is cooled, crushed and sieved to obtain the composite catalyst. Crushing the composite catalyst is beneficial for uniform mixing with the organic lithium.
[0047] The present invention also provides a positive electrode material lithium supplement, comprising an organic lithium salt and a composite catalyst as described in any one of the above embodiments, wherein the mass ratio of the organic lithium salt to the composite catalyst is 2-10, specifically 2, 4, 6, 8, 10 or any value between 2-10, while ensuring the catalytic effect, the content of lithium ions is increased as much as possible. In some embodiments, the mass ratio of the organic lithium salt to the composite catalyst is 6-9.
[0048] In some embodiments, the organic lithium salt is selected from at least one of lithium oxalate, lithium squarate and lithium citrate.
[0049] The addition of composite catalysts to the positive electrode material lithium supplement can improve the conductivity of the lithium supplement on the one hand, and on the other hand, it can reduce the decomposition potential of organic lithium salts, catalyze and accelerate the decomposition, thereby accelerating the Li + The released lithium ions move to nearby areas to supplement the loss of lithium ions during the formation stage. The decomposition of organic lithium salts also releases impurity gases such as carbon dioxide, which can be discharged from the battery during formation. The remaining lithium ions can effectively compensate for the low initial coulombic efficiency and poor cycle stability caused by the irreversible consumption of lithium ions during the initial charge and discharge process.
[0050] The lithium-ion battery lithium supplement additive provided by the present invention is insensitive to air and moisture, is compatible with almost all current lithium-ion battery positive electrode materials, is widely applicable, and is of great significance for improving the initial coulombic efficiency and cycle life of lithium-ion batteries.
[0051] An embodiment of the present invention further provides a method for preparing the positive electrode material lithium supplement agent described in the aforementioned embodiment, comprising: mixing the organic lithium salt and the composite catalyst by a solid phase mixing method and a liquid phase mixing method to obtain the positive electrode material lithium supplement agent.
[0052] The preparation method is simple and only requires uniform mixing of the organic lithium salt and the composite catalyst, which is convenient for large-scale industrial application.
[0053] The specific mixing method includes solid phase mixing method and liquid phase mixing method, wherein the solid phase mixing method includes but is not limited to ball milling, high mixing and ploughshare mixing, and the liquid phase mixing method includes but is not limited to sand milling, spraying, etc. When the liquid phase mixing method is combined with spray drying technology, the composite uniformity between the catalyst and the lithium supplement additive can be improved, the conductivity can be improved, and the decomposition of the lithium supplement additive can be accelerated.
[0054] An embodiment of the present invention further provides a positive electrode material, comprising the positive electrode material lithium supplement agent described in the aforementioned embodiment.
[0055] An embodiment of the present invention provides a secondary battery, comprising the ternary positive electrode material described in any one of the aforementioned embodiments.
[0056] In the positive electrode sheet of the secondary battery, the positive electrode material layer usually contains the positive electrode material, a binder and a conductive agent, and is usually formed by coating the positive electrode slurry, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode material, the conductive agent and the binder in a solvent and stirring them evenly. The solvent can be N-methylpyrrolidone (NMP).
[0057] In some optional embodiments, based on the total weight of the positive electrode material layer, the positive electrode material layer may contain 70wt%-97wt% of the ternary positive electrode material. Optionally, the weight proportion of the ternary positive electrode material in the positive electrode material layer is 85%-97%, 90%-97%, or 95%-97%. By adjusting the proportion of the ternary positive electrode material in the positive electrode material layer, the energy density and cycle life of the lithium-ion battery can be further improved.
[0058] In some embodiments, the binder of the positive electrode material layer may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and modified polymers thereof.
[0059] The conductive agent can improve the electronic conductivity of the positive electrode material layer. In some optional embodiments, the positive electrode material layer may contain 2wt%-20wt% of the conductive agent based on the total weight of the positive electrode material layer. Optionally, the weight proportion of the conductive agent in the positive electrode material layer is 2%-10%, or 2%-5%.
[0060] In some embodiments, the conductive agent of the positive electrode material layer may include one or more of superconducting carbon, carbon black (such as Super P, acetylene black, Ketjen black), carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0061] The present invention provides a lithium-ion battery, comprising the positive electrode sheet described in the above embodiment, and also comprising a negative electrode sheet, an electrolyte and a separator.
[0062] [Negative electrode]
[0063] The negative electrode plate of the present invention comprises a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector.
[0064] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is laminated on any one or both of the two opposite surfaces of the negative electrode current collector.
[0065] The negative electrode current collector may be made of a material with good electrical conductivity and mechanical strength to perform the functions of conducting and collecting current. In some embodiments, the negative electrode current collector may be made of copper foil.
[0066] In the negative electrode sheet of the present invention, the negative electrode film layer generally comprises a negative electrode active material, a binder, a conductive agent and other optional additives. It is generally formed by coating a negative electrode slurry on a negative electrode current collector, drying and cold pressing. The negative electrode slurry is generally formed by dispersing a negative electrode positive electrode material, an optional conductive agent, an optional binder, an optional additive, etc. in a solvent and stirring them uniformly. The solvent may be N-methylpyrrolidone (NMP) or deionized water.
[0067] In some embodiments, the negative electrode active material may include one or more of artificial graphite, natural graphite, silicon-based materials, and tin-based materials. Alternatively, the negative electrode active material includes one or more of artificial graphite and natural graphite. Alternatively, the negative electrode active material includes artificial graphite.
[0068] In some embodiments, the conductive agent may include one or more of superconducting carbon, carbon black (eg, Super P, acetylene black, Ketjen black, etc.), carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0069] In some embodiments, the binder may include one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).
[0070] In some embodiments, other optional auxiliary agents include, for example, a thickener (eg, sodium carboxymethyl cellulose CMC-Na), a PTC thermistor material, and the like.
[0071] [Electrolytes]
[0072] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present invention has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be selected from an electrolyte. The electrolyte includes an electrolyte salt and a solvent.
[0073] In some embodiments, the electrolyte salt can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0074] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0075] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.
[0076] [Isolation film]
[0077] The separator is disposed between the positive electrode sheet and the negative electrode sheet to play a role of isolation. The lithium ion battery of the present invention has no particular restrictions on the type of separator, and any known porous structure separator for lithium ion batteries can be selected. For example, the separator can be selected from one or more of a glass fiber film, a non-woven film, a polyethylene film, a polypropylene film, a polyvinylidene fluoride film, and a multilayer composite film containing one or more of them.
[0078] The positive electrode sheet, the negative electrode sheet and the isolation film can be made into an electrode assembly through a lamination process or a winding process, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolation role; the electrode assembly is placed in an outer package, the electrolyte is injected and sealed, and a lithium-ion battery can be obtained.
[0079] The outer packaging of the lithium-ion battery is used to encapsulate the electrode assembly and the electrolyte. In some embodiments, the outer packaging of the lithium-ion battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the lithium-ion battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0080] The present invention has no particular limitation on the shape of the lithium-ion battery, which may be cylindrical, square or any other shape.
[0081] In some embodiments, lithium-ion batteries may be assembled into a battery module. The battery module may contain multiple lithium-ion batteries, and the specific number may be adjusted according to the application and capacity of the battery module.
[0082] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0083] The present invention provides an electrical device, comprising the secondary battery described in the above embodiment.
[0084] The present invention also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack described in the present invention. The secondary battery, battery module or battery pack can be used as a power source for the device, or as an energy storage unit for the device. The device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc. The device can select a secondary battery, a battery module or a battery pack according to its use requirements.
[0085] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0086] Example 1
[0087] This embodiment provides a method for preparing a composite lithium supplement additive, which specifically includes the following steps:
[0088] Step S1: 120 g Super P conductive carbon, 10 g nickelous oxide and 300 g melamine were dispersed and added into a ball mill, and the materials were mixed by ball milling at a ball milling speed of 300 rpm, a bead to material ratio of 5:1, and a ball milling time of 3 h to obtain the material to be fired.
[0089] Step S2: The material to be sintered is placed in a nitrogen-saturated box furnace for sintering at a heating rate of 5°C / min, a holding temperature of 900°C, and a holding time of 3h. After cooling to ambient temperature, a nickel- and nitrogen-doped carbon-based catalyst is obtained.
[0090] Step S3: 5 g of the catalyst obtained in S2 and 45 g of lithium oxalate are added to a ball mill, and the mixture is mixed by ball milling at a ball milling speed of 300 rpm, a bead-to-material ratio of 5:1, and a ball milling time of 3 h to obtain a composite lithium supplement additive.
[0091] Example 2
[0092] This embodiment provides a method for preparing a composite lithium supplement additive, which is different from Embodiment 1 mainly in the type and amount of metal added, and specifically includes the following steps:
[0093] Step S1: 120 g Super P conductive carbon, 10.7 g cobalt tetroxide and 300 g melamine were dispersed and added into a ball mill, and the materials were mixed by ball milling at a ball milling speed of 300 rpm, a bead to material ratio of 5:1, and a ball milling time of 3 h to obtain the material to be fired.
[0094] Step S2: The material to be sintered is placed in a nitrogen-saturated box furnace for sintering at a heating rate of 5°C / min, a holding temperature of 900°C, and a holding time of 3h. After cooling to ambient temperature, a cobalt- and nitrogen-doped carbon-based catalyst is obtained.
[0095] Step S3: 5g of the catalyst obtained in S2 and 45g of lithium oxalate were added to a ball mill, and the mixture was mixed by ball milling at a speed of 300rpm, a bead-to-material ratio of 5:1, and a ball milling time of 3h to obtain a composite lithium supplement additive. The SEM image is as follows: Figure 1 .
[0096] Example 3
[0097] This embodiment provides a method for preparing a composite lithium supplement additive, which is different from Embodiment 1 mainly in that the type and amount of metal added are different, and specifically includes the following steps:
[0098] Step S1: 120 g Super P conductive carbon, 10.9 g manganese tetraoxide and 300 g melamine were dispersed and added into a ball mill, and the materials were mixed by ball milling at a ball milling speed of 300 rpm, a bead to material ratio of 5:1, and a ball milling time of 3 h to obtain the material to be fired.
[0099] Step S2: the material to be sintered is placed in a nitrogen-saturated box furnace for sintering at a heating rate of 5°C / min, a holding temperature of 900°C, a holding time of 3h, and then cooled to ambient temperature to obtain a manganese and nitrogen-doped carbon-based catalyst.
[0100] Step S3: 5 g of the catalyst obtained in S2 and 45 g of lithium oxalate are added to a ball mill, and the mixture is mixed by ball milling at a ball milling speed of 300 rpm, a bead-to-material ratio of 5:1, and a ball milling time of 3 h to obtain a composite lithium supplement additive.
[0101] Example 4
[0102] This embodiment provides a method for preparing a composite lithium supplement additive, which is different from Embodiment 2 mainly in that the type of conductive carbon material is different, and specifically includes the following steps:
[0103] Step S1: Add 120g of Ketjen Black EC-600JD conductive carbon, 10.7g of cobalt tetroxide and 300g of melamine into a ball mill, and mix the materials by ball milling. The ball milling speed is 300rpm, the bead-to-material ratio is 5:1, and the ball milling time is 3h to obtain the material to be fired.
[0104] Step S2: The material to be sintered is placed in a nitrogen-saturated box furnace for sintering at a heating rate of 5°C / min, a holding temperature of 900°C, and a holding time of 3h. After cooling to ambient temperature, a cobalt- and nitrogen-doped carbon-based catalyst is obtained.
[0105] Step S3: 5 g of the catalyst obtained in S2 and 45 g of lithium oxalate are added to a ball mill, and the mixture is mixed by ball milling at a ball milling speed of 300 rpm, a bead-to-material ratio of 5:1, and a ball milling time of 3 h to obtain a composite lithium supplement additive.
[0106] Example 5
[0107] This embodiment provides a preparation method of a composite lithium supplement additive, which is different from Embodiment 4 mainly in that the mixing method of lithium oxalate and the catalyst is different, and specifically includes the following steps:
[0108] Step S1: Add 120g of Ketjen Black EC-600JD conductive carbon, 10.7g of cobalt tetroxide and 300g of melamine into a ball mill, and mix the materials by ball milling. The ball milling speed is 300rpm, the bead-to-material ratio is 5:1, and the ball milling time is 3h to obtain the material to be fired.
[0109] Step S2: The material to be sintered is placed in a nitrogen-saturated box furnace for sintering at a heating rate of 5°C / min, a holding temperature of 900°C, and a holding time of 3h. After cooling to ambient temperature, a cobalt- and nitrogen-doped carbon-based catalyst is obtained.
[0110] Step S3: 50g of the catalyst obtained in S2 and 450g of lithium oxalate are dispersed in 25kg of pure water, and then poured into a sand mill and mixed for 30 minutes to obtain a mixed slurry of the catalyst and lithium oxalate. The mixed slurry is spray dried at 210°C and a flow rate of 5L / h to obtain a composite lithium supplement additive, as shown in the SEM image. Figure 2 .
[0111] Example 6
[0112] This embodiment provides a method for preparing a composite lithium supplement additive, which is different from Embodiment 5 mainly in that the sintering temperature is slightly lower, and specifically comprises the following steps:
[0113] Step S1: Add 120g of Ketjen Black EC-600JD conductive carbon, 10.7g of cobalt tetroxide and 300g of melamine into a ball mill, and mix the materials by ball milling. The ball milling speed is 300rpm, the bead-to-material ratio is 5:1, and the ball milling time is 3h to obtain the material to be fired.
[0114] Step S2: The material to be sintered is placed in a nitrogen-saturated box furnace for sintering at a heating rate of 5°C / min, a holding temperature of 700°C, and a holding time of 3h. After cooling to ambient temperature, a cobalt- and nitrogen-doped carbon-based catalyst is obtained.
[0115] Step S3: 50g of the catalyst obtained in S2 and 450g of lithium oxalate are dispersed in 25kg of pure water, and then poured into a sand mill and sand-milled for 30 minutes to obtain a mixed slurry of the catalyst and lithium oxalate. The mixed slurry is spray-dried at 210°C and a flow rate of 5L / h to obtain a composite lithium supplement additive.
[0116] Example 7
[0117] This embodiment provides a method for preparing a composite lithium supplement additive, which is different from Embodiment 5 mainly in that the sintering temperature is slightly lower, and specifically comprises the following steps:
[0118] Step S1: add 120g of Ketjen Black EC-600JD conductive carbon, 10.7g of cobalt tetroxide and 300g of melamine to a ball mill, and mix the materials by ball milling. The ball milling speed is 300rpm, the bead-to-material ratio is 5:1, and the ball milling time is 3h to obtain the material to be fired.
[0119] Step S2: The material to be sintered is placed in a nitrogen-saturated box furnace for sintering at a heating rate of 5°C / min, a holding temperature of 800°C, and a holding time of 3h. After cooling to ambient temperature, a cobalt- and nitrogen-doped carbon-based catalyst is obtained.
[0120] Step S3: 50g of the catalyst obtained in S2 and 450g of lithium oxalate are dispersed in 25kg of pure water, and then poured into a sand mill and sand-milled for 30 minutes to obtain a mixed slurry of the catalyst and lithium oxalate. The mixed slurry is spray-dried at 210°C and a flow rate of 5L / h to obtain a composite lithium supplement additive.
[0121] Example 8
[0122] This embodiment provides a method for preparing a composite lithium supplement additive, which is different from Embodiment 5 mainly in that the sintering temperature is slightly higher, and specifically includes the following steps:
[0123] Step S1: add Ketjen Black EC-600JD conductive carbon, 10.7 g of cobalt tetroxide and 300 g of melamine to a ball mill, and mix the materials by ball milling. The ball milling speed is 300 rpm, the bead-to-material ratio is 5:1, and the ball milling time is 3 h to obtain the material to be fired.
[0124] Step S2: The material to be sintered is placed in a nitrogen-saturated box furnace for sintering at a heating rate of 5°C / min, a holding temperature of 1000°C, and a holding time of 3h. After cooling to ambient temperature, a cobalt- and nitrogen-doped carbon-based catalyst is obtained.
[0125] Step S3: 50g of the catalyst obtained in S2 and 450g of lithium oxalate are dispersed in 25kg of pure water, and then poured into a sand mill and sand-milled for 30 minutes to obtain a mixed slurry of the catalyst and lithium oxalate. The mixed slurry is spray-dried at 210°C and a flow rate of 5L / h to obtain a composite lithium supplement additive.
[0126] Example 9
[0127] This embodiment provides a method for preparing a composite lithium supplement additive, which is different from Embodiment 5 mainly in that the content of cobalt tetroxide in the catalyst raw material is reduced, and specifically comprises the following steps:
[0128] Step S1: Add 120g of Ketjen Black EC-600JD conductive carbon, 7.5g of cobalt tetroxide and 300g of melamine into a ball mill, and mix the materials by ball milling. The ball milling speed is 300rpm, the bead-to-material ratio is 5:1, and the ball milling time is 3h to obtain the material to be fired.
[0129] Step S2: The material to be sintered is placed in a nitrogen-saturated box furnace for sintering at a heating rate of 5°C / min, a holding temperature of 900°C, and a holding time of 3h. After cooling to ambient temperature, a cobalt- and nitrogen-doped carbon-based catalyst is obtained.
[0130] Step S3: 50g of the catalyst obtained in S2 and 450g of lithium oxalate are dispersed in 25kg of pure water, and then poured into a sand mill and sand-milled for 30 minutes to obtain a mixed slurry of the catalyst and lithium oxalate. The mixed slurry is spray-dried at 210°C and a flow rate of 5L / h to obtain a composite lithium supplement additive.
[0131] Example 10
[0132] This embodiment provides a method for preparing a composite lithium supplement additive, which is different from Embodiment 5 mainly in that the content of cobalt tetroxide in the catalyst raw material is increased, and specifically comprises the following steps:
[0133] Step S1: Add 120g of Ketjen Black EC-600JD conductive carbon, 13.9g of cobalt tetroxide and 300g of melamine into a ball mill, and mix the materials by ball milling. The ball milling speed is 300rpm, the bead-to-material ratio is 5:1, and the ball milling time is 3h to obtain the material to be fired.
[0134] Step S2: The material to be sintered is placed in a nitrogen-saturated box furnace for sintering at a heating rate of 5°C / min, a holding temperature of 900°C, and a holding time of 3h. After cooling to ambient temperature, a cobalt- and nitrogen-doped carbon-based catalyst is obtained.
[0135] Step S3: 50g of the catalyst obtained in S2 and 450g of lithium oxalate are dispersed in 25kg of pure water, and then poured into a sand mill and sand-milled for 30 minutes to obtain a mixed slurry of the catalyst and lithium oxalate. The mixed slurry is spray-dried at 210°C and a flow rate of 5L / h to obtain a composite lithium supplement additive. Figure 3 The XRD spectrum did not detect any diffraction peaks of other phases, and the main body of the material was lithium oxalate phase.
[0136] Comparative Example 1
[0137] This comparative example provides a method for preparing a composite lithium supplement additive, which is different from Example 5 mainly in that the catalyst raw material does not contain cobalt tetroxide, and specifically comprises the following steps:
[0138] Step S1: Add 120g of Ketjen Black EC-600JD conductive carbon and 300g of melamine into a ball mill, and mix the materials by ball milling. The ball milling speed is 300rpm, the bead-to-material ratio is 5:1, and the ball milling time is 3h to obtain the material to be fired.
[0139] Step S2: The material to be sintered is placed in a nitrogen-saturated box furnace for sintering at a heating rate of 5°C / min, a holding temperature of 900°C, and a holding time of 3h. The nitrogen-doped carbon-based catalyst is then obtained after cooling to ambient temperature.
[0140] Step S3: 50g of the catalyst obtained in S2 and 450g of lithium oxalate are dispersed in 25kg of pure water, and then poured into a sand mill and sand-milled for 30 minutes to obtain a mixed slurry of the catalyst and lithium oxalate. The mixed slurry is spray-dried at 210°C and a flow rate of 5L / h to obtain a composite lithium supplement additive.
[0141] Comparative Example 2
[0142] This comparative example provides a preparation method of a composite lithium supplement additive, which is different from Example 5 mainly in that cobalt tetraoxide in the catalyst raw material is replaced by molybdenum trioxide, and specifically comprises the following steps:
[0143] Step S1: Add 120g of Ketjen black conductive carbon, 11.8g of molybdenum trioxide and 300g of melamine into a ball mill, and mix the materials by ball milling. The ball milling speed is 300rpm, the bead-to-material ratio is 5:1, and the ball milling time is 3h to obtain the material to be fired.
[0144] Step S2: The material to be sintered is placed in a nitrogen-saturated box furnace for sintering at a heating rate of 5°C / min, a holding temperature of 900°C, and a holding time of 3h. After cooling to ambient temperature, a molybdenum- and nitrogen-doped carbon-based catalyst is obtained.
[0145] Step S3: 50g of the catalyst obtained in S2 and 450g of lithium oxalate are dispersed in 25kg of pure water, and then poured into a sand mill and sand-milled for 30 minutes to obtain a mixed slurry of the catalyst and lithium oxalate. The mixed slurry is spray-dried at 210°C and a flow rate of 5L / h to obtain a composite lithium supplement additive.
[0146] Comparative Example 3
[0147] Commercial lithium oxalate was used as a positive electrode lithium supplement additive and sieved through a 200-mesh sieve as comparative example 3.
[0148] Comparative Example 4
[0149] This comparative example provides a lithium iron phosphate positive electrode material with a lithium supplement agent addition amount of 0%.
[0150] Comparative Example 5
[0151] This comparative example provides a method for preparing a composite lithium supplement additive, which is different from Example 5 mainly in that the catalyst raw material does not contain conductive carbon, and specifically comprises the following steps:
[0152] Step S1: Add 10.7 g of cobalt trioxide and 300 g of melamine into a ball mill, and mix the materials by ball milling. The ball milling speed is 300 rpm, the bead-to-material ratio is 5:1, and the ball milling time is 3 h to obtain the material to be fired.
[0153] Step S2: The material to be sintered is placed in a nitrogen-saturated box furnace for sintering at a heating rate of 5°C / min, a holding temperature of 900°C, and a holding time of 3h. The nitrogen-doped carbon-based catalyst is then obtained after cooling to ambient temperature.
[0154] Step S3: 50g of the catalyst obtained in S2 and 450g of lithium oxalate are dispersed in 25kg of pure water, and then poured into a sand mill and sand-milled for 30 minutes to obtain a mixed slurry of the catalyst and lithium oxalate. The mixed slurry is spray-dried at 210°C and a flow rate of 5L / h to obtain a composite lithium supplement additive.
[0155] Comparative Example 6
[0156] This comparative example provides a method for preparing a composite lithium supplement additive, which is different from Example 5 mainly in that the catalyst raw material does not contain melamine, and specifically comprises the following steps:
[0157] Step S1: Add 120g of Ketjen black conductive carbon and 10.7g of cobalt tetroxide into a ball mill, and mix the materials by ball milling. The ball milling speed is 300rpm, the bead-to-material ratio is 5:1, and the ball milling time is 3h to obtain the material to be fired.
[0158] Step S2: The material to be sintered is placed in a nitrogen-saturated box furnace for sintering at a heating rate of 5°C / min, a holding temperature of 900°C, and a holding time of 3h. After cooling to ambient temperature, a cobalt-doped carbon-based catalyst is obtained.
[0159] Step S3: 50g of the catalyst obtained in S2 and 450g of lithium oxalate are dispersed in 25kg of pure water, and then poured into a sand mill and sand-milled for 30 minutes to obtain a mixed slurry of the catalyst and lithium oxalate. The mixed slurry is spray-dried at 210°C and a flow rate of 5L / h to obtain a composite lithium supplement additive.
[0160] The steps for assembling and testing lithium-ion battery button half-cells are as follows:
[0161] The lithium supplement additive, polyvinylidene fluoride and Super P conductive additive were dispersed in N-methylpyrrolidone at a mass ratio of 90:5:5, stirred and coated on the surface of aluminum foil, and dried to obtain the positive electrode sheet. The lithium sheet, separator, positive electrode sheet and electrolyte were then assembled into a button battery half-cell for positive electrode sheet testing. The button battery model is CR2430, the separator material is polypropylene, and the electrolyte is a 1 mol / L lithium hexafluorophosphate solution (the solvent is a mixture of ethylene carbonate and propylene carbonate in a volume ratio of 1:1, and the solvent also contains 5wt% fluoroethylene carbonate).
[0162] The steps for assembling and testing lithium-ion soft-pack batteries are as follows:
[0163] The lithium supplement additives and lithium iron phosphate positive electrode materials (mass ratio of 3:97), polyvinylidene fluoride and Super P conductive additives prepared in each embodiment and comparative example are dispersed in N-methylpyrrolidone at a mass ratio of 90:5:5, and stirred to obtain a positive electrode slurry for a lithium ion battery. Then the surface of the aluminum foil is coated and the positive electrode sheet is obtained after complete drying. Graphite, polyvinylidene fluoride and Super are dispersed in ultrapure water, stirred to obtain a negative electrode slurry for a lithium ion battery, and then the surface of the copper foil is coated and the negative electrode sheet is obtained after drying. The negative electrode sheet, diaphragm, positive electrode sheet and electrolyte are then assembled into a soft-pack full battery for electrochemical performance testing. The button battery model used is CR2430, the diaphragm model is GF / C, and the electrolyte is a 1 mol / L lithium hexafluorophosphate solution (the solvent is a mixture of ethylene carbonate and propylene carbonate in a volume ratio of 1:1, and the solvent also contains 5wt% fluoroethylene carbonate). After assembly, the battery is removed from the glove box and tested after standing at 25°C for 8 hours.
[0164] Electrochemical properties of lithium-ion battery positive electrode:
[0165] Table 1 shows the electrical properties of the positive electrode sheets assembled with the composite additives prepared in Examples 1-10 and Comparative Examples 1-5. Figure 4 This is the first charge curve of the positive electrode sheet of the lithium ion battery additive, and the voltage range is 2.8V-4.3V. It can be seen from the table that the electrochemical performance of the positive electrode sheet in the embodiment is significantly better than that in the comparative example, among which the composite catalyst performance in Example 5 is the best, with a decomposition voltage of 4.08V, which can almost reach the theoretical capacity of lithium oxalate decomposition. From the comparison of Examples 1-3, it can be found that the catalytic effects of the three elements Ni, Co and Mn are Co>Ni>Mn from high to low. Figure 1 and Figure 2 It can be observed from the SEM image that the uniformity of Example 5 is greatly improved compared with that of Example 2 obtained by ball milling. The difference in electrochemical performance shows that the spray drying process can improve the uniformity of material composite and improve the electrochemical performance. By comparing Example 5 with Comparative Example 1 and Comparative Example 5 with Comparative Example 6, it can be found that there is a significant synergistic effect among the conductive carbon, nitrogen element and metal catalyst, and the lack of any one of them will lead to a loss of electrochemical performance.
[0166] Table 1 Comparison of electrochemical properties of lithium-ion battery positive electrodes
[0167] First charge specific capacity (mAh / g) Average charging voltage(V) Example 1 488.2 4.18 Example 2 500.8 4.15 Example 3 475.3 4.2 Example 4 514.6 4.12 Example 5 524.5 4.08 Example 6 468.2 4.21 Example 7 493.2 4.16 Example 8 467.6 4.21 Example 9 480.5 4.20 Example 10 512.6 4.13 Comparative Example 1 426.4 4.29 Comparative Example 2 465.8 4.21 Comparative Example 3 320.2 4.31 Comparative Example 5 353.4 4.62 Comparative Example 6 362.8 4.48
[0168] The electrical performance of soft-pack batteries with lithium iron phosphate as the positive electrode material and composite lithium supplement additives:
[0169] Table 2 shows the electrical properties of the composite lithium supplement additives prepared in Examples 1-10 and Comparative Examples 1-3, 5 and 6 after mixing with the lithium iron phosphate positive electrode. The formation voltage test range is 2.5V-4.3V, the rate is 0.1C, and then the cycle voltage test range is changed to 2.5V-3.65V, the rate is 1C. Figure 5 The discharge capacity retention rate of the soft-pack battery assembled in Example 5 and Comparative Example 4. From Table 2 and Figure 5 It can be seen that the initial discharge specific capacity of the positive electrode sheet in the embodiment is significantly better than that of the comparative example, among which the initial discharge specific capacity of Example 5 is the highest, reaching 162.5 mAh / g, and the capacity retention rate after 100 cycles can reach 94.2%, which is far higher than that of the comparative example, indicating that the lithium replenishing additive prepared by the present invention has a good lithium replenishing effect.
[0170] Table 2 Comparison of electrical properties of soft-pack batteries with lithium iron phosphate as the positive electrode material and composite lithium supplement additives
[0171]
[0172] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A composite catalyst for decomposing a positive electrode material lithium supplement, characterized in that: It includes nitrogen-doped conductive carbon and a metal element, wherein the metal element is selected from at least one of nickel element, cobalt element and manganese element, and the nitrogen in the nitrogen-doped conductive carbon exists in the form of at least one of pyridinic nitrogen, pyrrolic nitrogen, graphitic nitrogen and nitrogen oxide groups.
2. The composite catalyst for decomposing a positive electrode material lithium supplement according to claim 1, characterized in that: The mass fraction of the metal element in the composite catalyst is 1wt%-20wt%; And / or, the mass fraction of nitrogen in the composite catalyst is 1wt%-4wt%.
3. The composite catalyst for decomposing a positive electrode material lithium supplement according to claim 1, characterized in that: The mass fraction of the metal element in the composite catalyst is 3wt%-11wt%; And / or, the mass fraction of nitrogen in the composite catalyst is 1.5wt%-3wt%.
4. A method for preparing a composite catalyst for decomposing a positive electrode material lithium supplement according to any one of claims 1 to 3, characterized in that: include: The composite catalyst is obtained by sintering a mixture of a conductive carbon material, a nitrogen-containing organic matter and a metal source corresponding to a metal element, and the sintering atmosphere is an inert gas.
5. The method for preparing the composite catalyst for decomposing the positive electrode material lithium supplement according to claim 4, characterized in that: The conductive carbon material is selected from at least one of carbon nanotubes, acetylene black, activated carbon, Ketjen black, mesoporous carbon and graphene; And / or, the nitrogen-containing organic matter is selected from at least one of melamine, dicyandiamide and urea; And / or, the metal source is a metal oxide; And / or, the preparation of the mixture comprises: mixing the conductive carbon material, the nitrogen-containing organic matter and the metal source by a solid phase mixing method.
6. The method for preparing the composite catalyst for decomposing the positive electrode material lithium supplement according to claim 4, characterized in that: The sintering step temperature is 600°C-1100°C, the time is 1h-5h, and the sintering atmosphere is an inert atmosphere; and / or, the heating rate of the sintering step is 2°C / min-9°C / min; And / or, after the sintering step, the sintered product is cooled, crushed and sieved to obtain the composite catalyst.
7. A positive electrode material lithium supplement, characterized in that: It comprises an organic lithium salt and the composite catalyst according to any one of claims 1 to 3, wherein the mass ratio of the organic lithium salt to the composite catalyst is 2-10.
8. The positive electrode material lithium supplement according to claim 7, characterized in that: The mass ratio of the organic lithium salt to the composite catalyst is 6-9; And / or, the organic lithium salt is selected from at least one of lithium oxalate, lithium squarate and lithium citrate.
9. A method for preparing a positive electrode material lithium supplement according to claim 7 or 8, characterized in that: include: The organic lithium salt and the composite catalyst are mixed by a solid phase mixing method and a liquid phase mixing method to obtain the positive electrode material lithium supplement agent.
10. A positive electrode material, characterized in that: The invention comprises the positive electrode material lithium supplement agent as described in claim 7 or 8.
Citation Information
Cited By
Water-based lithium-supplementing diaphragm and preparation method and application thereof
CN119905772A
Aqueous lithium supplementing diaphragm, preparation method and application thereof
CN119905772B